2006
DOI: 10.1089/sur.2006.7.373
|View full text |Cite
|
Sign up to set email alerts
|

Infection after Fingertip Injury in Children

Abstract: We describe two cases of severe infectious complications after trauma to the finger phalanges in children: osteoarticular infection of the thumb and phlegmon of the thumb's long flexor sheath. These complications are rare after such injuries, which are common and for which the appropriate treatment is often an issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Failure to repair such lacerations, they argued, increased the risk for permanent cosmetic and functional abnormalities, such as nail streaks and depressions, abnormal nail plate regrowth, or nail splits 9 . Subsequent studies have demonstrated, however, that trephination alone should suffice for the treatment of uncomplicated subungual hematomas, regardless of size 1,2,10,11 . The procedure is quick, cost鈥恊ffective, and poses minimal structural or infectious risk as long the nail bed is not violated.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to repair such lacerations, they argued, increased the risk for permanent cosmetic and functional abnormalities, such as nail streaks and depressions, abnormal nail plate regrowth, or nail splits 9 . Subsequent studies have demonstrated, however, that trephination alone should suffice for the treatment of uncomplicated subungual hematomas, regardless of size 1,2,10,11 . The procedure is quick, cost鈥恊ffective, and poses minimal structural or infectious risk as long the nail bed is not violated.…”
Section: Discussionmentioning
confidence: 99%